Pengabdian Kepada Masyarakat untuk Peningkatan Industri Uis Karo di Sumatera Utara - Riah Ukur Ginting; Salomo Sijabat; Dini Maria Hutagalung; Eva Margaret Sarah Nainggolan; Rianto Sitanggang (Pelita Masyarakat, 2020)
Uis Karo as a traditional cloth, is one of the local wisdoms in North Sumatera. The business has a good prospect for local people income and for the North Sumatera Province also. The business activities require workers which can create job demands for the local people. The patterns, design and colors of Uis Karo are very unique. It has special demand in the business market. Trias Tambun Galery and Ketang Craftman still need strategy and effort to improve their products and quality, such as appropriate technology, knowlegde to improve the quantity and quality of the product therefore they can compete in local or national market. The technology, knowledge and skillful are needed to help them to raise their business profit. Therefore those two home industries needs training and workshop to help them to undertand how to market and to produce their product efective and efficiently.  Therefore, the community partnership program is needed to help and assist those partners to raise their profit. There are three program activities, which are: a) Program to help the craftman to apply the right technology to increase the product. b) Program to help the partners to build e-commerce as an online marketing to spread out the sales and distribution of the products. The method of the programs are tutorial and workshop.